Copper-containing mesoporous molecular sieve complexing adsorbent as well as preparation and application thereof
The high-dispersed active-site adsorbent prepared by using lanthanum-doped mesoporous silica raw powder in olefin/alkane separation, and the formation of monovalent copper active sites is achieved through low-temperature reduction reaction, which solves the problems of active site aggregation and pore blockage, improves the separation performance and realizes the in-situ regeneration of the adsorbent.
Patent Information
- Application Number
- CN202411682153.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art has problems of active site aggregation and pore blockage in the olefin/alkane separation, resulting in a decrease in adsorption performance. The reduction process of cuprous oxide has the disadvantages of high temperature and difficult to control, making it difficult to achieve low temperature controllable divalent copper reduction.
By using the threshold space in the lanthanum doped mesoporous silica raw powder and the action between the lanthanum element and the complex active site, a mesoporous complex adsorbent with high dispersive active site was prepared, and a reduction reaction was carried out in the olefin gas stream to obtain a high content of monovalent copper active site at low temperature.
The separation performance of adsorbent in olefin/alkane separation is improved, the in-situ regeneration of adsorbent is achieved, the problems of large equipment investment and high energy consumption are avoided, and the service life of adsorbent is extended.
Abstract
Description
Technical Field
[0001] The present invention relates to an adsorbent and its preparation and application, and more specifically to a copper-containing mesoporous molecular sieve complex adsorbent with highly dispersed active sites for olefin-alkane separation and its preparation and application, belonging to the technical field of chemical gas separation. Background Art
[0002] Ethylene is one of the world's largest chemical products. The ethylene industry is the core of the petrochemical industry and occupies an important position in the national economy. Olefins / alkanes are important raw materials in the petrochemical industry. Since the two have similar physical properties, the conditions for separating the two substances are extremely harsh. It is difficult to separate olefins / alkanes by relatively mild physical methods. In the existing process of dehydrogenating alkanes to prepare olefins, low-temperature distillation is often used to separate the two. It is necessary to frequently increase the pressure of high-temperature olefin materials and reduce it to minus 100 to 200°C, and then perform distillation separation operations. This operation requires large equipment investment and high energy consumption, resulting in huge energy consumption.
[0003] Adsorption separation has attracted wide attention due to its mild operating conditions, simple and efficient process, energy saving and low cost. The development of an adsorbent with large adsorption capacity and high adsorption selectivity remains the focus of adsorbent research. Studies have found that the active sites of the adsorbent can form complexing forces with unsaturated bonds. This force, which is stronger than the van der Waals force and weaker than the chemical force, can selectively adsorb olefins at higher concentrations and desorb them in time at low concentrations. Active site porous adsorbents with this property can be used as complexing adsorbents in olefin / alkane separation.
[0004] However, in the prior art, the adsorbent is directly prepared by using a carrier without a template and a metal precursor without metal doping, which will result in no interaction between the active site and the carrier. In addition, due to the lack of a threshold space, the active site is easily aggregated, resulting in pore blockage, and the active site effect cannot be maximized, which greatly reduces the adsorption performance. Since cuprous oxide has a good effect on the separation of olefins / alkanes, the cuprous oxide on the adsorbent currently used is generally obtained by two methods: (1) the carrier loaded with copper oxide is heat-treated and reduced at high temperature (>700°C) in an inert atmosphere. This method has the disadvantages of high reduction temperature and long time; (2) the carrier loaded with copper oxide is heat-treated in a reducing atmosphere (H2 or CO). This method has the disadvantage of being difficult to control the degree of reduction, and it is easy to reduce to copper. Therefore, developing a new method for preparing a copper-containing adsorbent to achieve controllable reduction of divalent copper to monovalent copper at low temperature is the key to solving the problems existing in the prior art.
[0005] In addition, when traditional adsorbents become deactivated during use, they need to be removed from the device and reactivated and regenerated, which requires a lot of manpower and time; some people directly replace new adsorbents, resulting in material waste. Due to the unique redox properties of monovalent copper, monovalent copper adsorbents that can be regenerated in situ can greatly improve the efficiency of the production process and solve the problem of adsorbent service life from the root. Summary of the invention
[0006] The purpose of the present invention is: to address the problems existing in the prior art, to provide a method for preparing a copper-containing mesoporous molecular sieve complex adsorbent with highly dispersed active sites, another purpose of the present invention is to provide an adsorbent prepared by the above method, another purpose of the present invention is to provide the application of the above adsorbent in olefin / alkane separation, and another purpose of the present invention is to provide a regeneration method for the above adsorbent; the preparation method of the copper-containing mesoporous molecular sieve complex adsorbent can achieve a higher content of monovalent copper active sites with lower energy consumption and in a shorter time, thereby improving the separation performance of the adsorbent in olefin / alkane separation, and at the same time provides a convenient operation method for a copper-containing adsorbent that can be activated in situ when the adsorbent is deactivated.
[0007] The technical solution of the present invention is as follows:
[0008] By utilizing the limited space in the lanthanum-doped mesoporous silica powder and the interaction between the lanthanum element and the complex active site, the complex active site is highly dispersed to prepare a mesoporous complex adsorbent with highly dispersed active sites; the complex active site is Cu + .
[0009] As a preferred embodiment of a mesoporous complex adsorbent with highly dispersed active sites described in the present invention, the lanthanum-doped mesoporous silica raw powder refers to lanthanum-doped mesoporous silica from which the template has not been removed; the threshold space refers to the special space formed between the template and the silicon wall in the mesoporous silica raw powder; the mesoporous silica is a type of material with ordered porous properties formed by supramolecular self-assembly of inorganic species constituting the silica skeleton in a solvent phase under the template action of a surfactant, including but not limited to one or more of SBA-15 and KIT-6.
[0010] The specific technical scheme of the present invention is: a method for preparing a copper-containing mesoporous molecular sieve complex adsorbent, and the specific steps are as follows:
[0011] 1) mixing a copper salt with a carrier, grinding them fully, and then heat treating them to obtain a mesoporous molecular sieve material with dispersed copper oxide; wherein the mass ratio of copper oxide to the carrier in the prepared mesoporous molecular sieve material with dispersed copper oxide is 0.1 to 1:1; the carrier is a lanthanum-doped mesoporous molecular sieve material with an orderly pore structure; wherein the molar ratio of lanthanum to silicon in the lanthanum-doped mesoporous molecular sieve material is 0.01 to 0.1;
[0012] 2) The mesoporous molecular sieve material dispersed with copper oxide obtained in step 1) is fixedly placed in a stable olefin gas flow to perform a reduction reaction to obtain a copper-containing mesoporous molecular sieve complex adsorbent.
[0013] Preferably, the copper salt in step 1) is copper nitrate or copper acetate; the heat treatment temperature is 300-600° C. and the time is 2-5 hours.
[0014] Preferably, the lanthanum-doped mesoporous molecular sieve material in step 1) is one or both of lanthanum-doped SBA-15 and KIT-6.
[0015] Preferably, the olefin in step 2) is ethylene or propylene.
[0016] Preferably, the reduction reaction temperature in step 2) is 100-160°C, the reaction time is 1-2h, and the mass space velocity of the olefin is 0.035-0.875h -1 .
[0017] The present invention also provides a copper-containing mesoporous molecular sieve complex adsorbent prepared by the above preparation method.
[0018] As one aspect of the present invention, the present invention overcomes the deficiencies in the prior art and provides the application of a mesoporous complex adsorbent with highly dispersed active sites, mainly for olefin / alkane separation. The present invention provides the application of the above-mentioned copper-containing mesoporous molecular sieve complex adsorbent in olefin / alkane adsorption separation.
[0019] As a preferred solution for the application of the mesoporous complex adsorbent with highly dispersed active sites described in the present invention, the olefin is ethylene or propylene; and the alkane is ethane or propane.
[0020] The monovalent copper active component is easily oxidized to divalent copper during the olefin / alkane separation process. Such adsorbents can be activated and regenerated in situ in the separation system by heating, without taking out the adsorbent. Therefore, the present invention also provides an in-situ activation and regeneration method for the above-mentioned copper-containing mesoporous molecular sieve adsorbent, which specifically comprises the following steps: heating a fixed bed equipped with a deactivated adsorbent to 100-160°C, and heating the fixed bed at a mass space velocity of 0.035-0.875h-1 at olefin mass space velocity of 0.035-0.875h-1. -1 The reaction was continued for 1 to 2 hours, and the deactivated adsorbent was regenerated in situ.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention utilizes the limited threshold space in the lanthanum-doped mesoporous silica raw powder and the interaction between the lanthanum element and the complex active site to highly disperse the complex active site, thereby preparing a mesoporous complex adsorbent with highly dispersed active sites. The preparation method is simple, and the complexing ability of the mesoporous silica can be significantly improved by doping with the lanthanum element, thereby significantly improving its selective adsorption performance for olefins. The present invention directly applies the complex adsorbent with highly dispersed active sites prepared by the above preparation method to the separation of olefins / alkanes, obtains a better separation effect, is easy to operate, has mild separation conditions, obtains a uniform reduction degree of metal oxides in the sample, greatly improves the selectivity of olefins, has a large adsorption capacity for olefins, and has a high adsorption separation efficiency. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0024] Embodiment 1:
[0025] Preparation method of lanthanum-doped SBA-15: Weigh 3g of P123, 22.5g of deionized water, 90g of HCl (2M), 6.38g of tetraethyl orthosilicate and 0.1g of lanthanum nitrate, place in a 40°C water bath and stir for 24h, then age the mixture at 100°C for 24h, cool naturally to room temperature, filter, wash and dry to obtain lanthanum-doped SBA-15 raw powder (lanthanum-silicon ratio is 0.01).
[0026] Preparation of adsorbent: Weigh 0.4837g (2mmol) of copper nitrate and 1g of La-SBA-15 raw powder with a lanthanum-silicon ratio of 0.01, grind them for 30min, heat treat them at 300℃ for 5h in air atmosphere, and obtain a sample loaded with copper oxide after cooling (the mass ratio of copper oxide to carrier is 0.32:1). Take 0.5g of the sample and fill it into a glass capillary, place it in a 110℃ tube furnace for 2h in an ethylene gas flow with a flow rate of 5.0mL / min, and obtain a mesoporous complex adsorbent with highly dispersed active sites after cooling.
[0027] Adsorption application experiment: The gas adsorption performance of the adsorbent was determined by the volumetric method. 500 mg of the above adsorbent was placed in the ASAP2020 specific surface and pore analyzer of Mack, USA, and adsorbed at room temperature and pressure. Finally, the adsorption of ethylene / ethane by the adsorbent was measured respectively, and the ethylene / ethane separation selectivity of the adsorbent was calculated. At room temperature and pressure, the adsorption of ethylene by the adsorbent was 4.37 mmol / g, the adsorption of ethane was 2.36 mmol / g, and the IAST selectivity was 24.3.
[0028] Embodiment 2:
[0029] According to the preparation method in Example 1, lanthanum-doped SBA-15 raw powder with a lanthanum-silicon ratio of 0.03 was prepared.
[0030] Preparation of adsorbent: Weigh 0.2589g (1.3mmol) of copper acetate and 0.5g of La-SBA-15 with a lanthanum-silicon ratio of 0.03, grind them for 30min, heat treat them at 400℃ in air atmosphere for 4.5h, and obtain a sample loaded with copper oxide after cooling (the mass ratio of copper oxide to carrier is 0.42:1). Take 0.4g of the sample and fill it into a glass capillary, place it in a 130℃ tube furnace and heat it for 2h in an ethylene gas flow of 4.5mL / min, and obtain a mesoporous complex adsorbent with highly dispersed active sites after cooling.
[0031] Adsorption application experiment: The gas adsorption performance of the adsorbent was determined by the volumetric method. 500 mg of the above adsorbent was placed in the ASAP2020 specific surface and pore analyzer of Mack, USA, and adsorbed at room temperature and pressure. Finally, the adsorption of ethylene / ethane by the adsorbent was measured respectively, and the ethylene / ethane separation selectivity of the adsorbent was calculated. At room temperature and pressure, the adsorption of ethylene by the adsorbent was 4.30 mmol / g, the adsorption of ethane was 2.27 mmol / g, and the IAST selectivity was 24.8.
[0032] Embodiment 3:
[0033] Preparation method of lanthanum-doped KIT-6: Weigh 4g of P123, 144g of deionized water, 7.4g of HCl (37%), 4g of n-butanol, 8.5g of tetraethyl orthosilicate and 0.7g of lanthanum nitrate, place in a 40°C water bath and stir for 24h, then age the mixture at 100°C for 24h, cool naturally to room temperature, filter, wash and dry to obtain lanthanum-doped KIT-6 raw powder (lanthanum-silicon ratio is 0.05).
[0034] Preparation of adsorbent: Weigh 0.4830g (2mmol) of copper nitrate and 1g of La-KIT-6 original powder with a lanthanum-silicon ratio of 0.05, grind them for 30min, heat treat them at 550℃ for 3h in air atmosphere, and obtain a sample loaded with copper oxide after cooling (the mass ratio of copper oxide to carrier is 0.32:1). Take 0.5g of the sample and fill it into a glass capillary, place it in a 120℃ tube furnace for 2h in a propylene gas flow with a flow rate of 3.0mL / min, and obtain a mesoporous complex adsorbent with highly dispersed active sites after cooling.
[0035] Adsorption application experiment: The gas adsorption performance of the adsorbent was determined by the volumetric method. 500 mg of the above adsorbent was placed in the ASAP2020 specific surface and pore analyzer of Mack, USA, and adsorbed at room temperature and pressure. Finally, the adsorption of ethylene / ethane by the adsorbent was measured respectively, and the ethylene / ethane separation selectivity of the adsorbent was calculated. At room temperature and pressure, the adsorption of ethylene by the adsorbent was 4.48 mmol / g, the adsorption of ethane was 2.33 mmol / g, and the IAST selectivity was 26.9.
[0036] Embodiment 4:
[0037] According to the preparation method in Example 3, lanthanum-doped KIT-6 raw powder with a lanthanum-silicon ratio of 0.06 was prepared.
[0038] Preparation of adsorbent: Weigh 0.3997g (2mmol) of copper acetate and 1g of La-KIT-6 with a lanthanum-silicon ratio of 0.06, grind them for 30min, heat treat them at 600℃ in air atmosphere for 2h, and obtain a sample loaded with copper oxide after cooling (the mass ratio of copper oxide to carrier is 0.32:1). Take 0.3g of the sample and fill it into a glass capillary, place it in a 150℃ tube furnace for 1h in a propylene gas flow with a flow rate of 3.5mL / min, and obtain a mesoporous complex adsorbent with highly dispersed active sites after cooling.
[0039] Adsorption application experiment: The gas adsorption performance of the adsorbent was determined by the volumetric method. 500 mg of the above adsorbent was placed in the ASAP2020 specific surface and pore analyzer of Mack, USA, and adsorbed at room temperature and pressure. Finally, the adsorption of ethylene / ethane by the adsorbent was measured respectively, and the ethylene / ethane separation selectivity of the adsorbent was calculated. At room temperature and pressure, the adsorption of ethylene by the adsorbent was 4.38 mmol / g, the adsorption of ethane was 2.18 mmol / g, and the IAST selectivity was 26.2.
[0040] Embodiment 5:
[0041] According to the preparation method in Example 1, lanthanum-doped SBA-15 raw powder with a lanthanum-silicon ratio of 0.06 was prepared.
[0042] Preparation of adsorbent: Weigh 0.2441g (1mmol) of copper nitrate and 1g of La-SBA-15 with a lanthanum-silicon ratio of 0.06, grind them for 30min, heat treat them at 400℃ in air atmosphere for 4h, and obtain a sample loaded with copper oxide after cooling (the mass ratio of copper oxide to carrier is 0.16:1). Take 0.3g of the sample and fill it into a glass capillary, place it in a 160℃ tube furnace for 1.5h in a propylene gas flow with a flow rate of 2.0mL / min, and obtain a mesoporous complex adsorbent with highly dispersed active sites after cooling.
[0043] Adsorption application experiment: The gas adsorption performance of the adsorbent was determined by the volumetric method. 500 mg of the above adsorbent was placed in the ASAP2020 specific surface and pore analyzer of Mack, USA, and adsorbed at room temperature and pressure. Finally, the adsorption amount of propylene / propane by the adsorbent was measured respectively, and the propylene / propane separation selectivity of the adsorbent was calculated. At room temperature and pressure, the adsorption amount of propylene by the adsorbent was 4.14 mmol / g, the adsorption amount of propane was 2.12 mmol / g, and the IAST selectivity was 24.1.
[0044] Embodiment 6:
[0045] According to the preparation method in Example 1, lanthanum-doped SBA-15 raw powder with a lanthanum-silicon ratio of 0.04 was prepared.
[0046] Preparation of adsorbent: Weigh 0.5962g (3mmol) of copper acetate and 0.5g of La-SBA-15 with a lanthanum-silicon ratio of 0.04, grind them for 30min, heat treat them at 500℃ for 3h in air atmosphere, and obtain a sample loaded with copper oxide after cooling (the mass ratio of copper oxide to carrier is 0.96:1). Take 0.3g of the sample and fill it into a glass capillary, place it in a 130℃ tube furnace for 2h in a propylene gas flow with a flow rate of 2.5mL / min, and obtain a mesoporous complex adsorbent loaded with highly dispersed active sites after cooling.
[0047] Adsorption application experiment: The gas adsorption performance of the adsorbent was determined by the volumetric method. 500 mg of the above adsorbent was placed in the ASAP2020 specific surface and pore analyzer of Mack, USA, and adsorbed at room temperature and pressure. Finally, the adsorption amount of propylene / propane by the adsorbent was measured respectively, and the propylene / propane separation selectivity of the adsorbent was calculated. At room temperature and pressure, the adsorption amount of propylene by the adsorbent was 4.02 mmol / g, the adsorption amount of propane was 2.42 mmol / g, and the IAST selectivity was 21.7.
[0048] Example 7
[0049] According to the preparation method in Example 3, lanthanum-doped KIT-6 raw powder with a lanthanum-silicon ratio of 0.04 was prepared.
[0050] Preparation of adsorbent: Weigh 0.4834g (2mmol) of copper nitrate and 1g of La-KIT-6 with a lanthanum-silicon ratio of 0.04, grind them for 30min, heat treat them at 400℃ in air atmosphere for 4.5h, and obtain a sample loaded with copper oxide after cooling (the mass ratio of copper oxide to carrier is 0.32:1). Take 0.3g of the sample and fill it into a glass capillary, place it in a 140℃ tube furnace for 1.5h in an ethylene gas flow with a flow rate of 6.0mL / min, and obtain a mesoporous complex adsorbent with highly dispersed active sites after cooling.
[0051] Adsorption application experiment: The gas adsorption performance of the adsorbent was determined by the volumetric method. 500 mg of the above adsorbent was placed in the ASAP2020 specific surface and pore analyzer of Mack, USA, and adsorbed at room temperature and pressure. Finally, the adsorption amount of propylene / propane by the adsorbent was measured respectively, and the propylene / propane separation selectivity of the adsorbent was calculated. At room temperature and pressure, the adsorption amount of propylene by the adsorbent was 4.75 mmol / g, the adsorption amount of propane was 2.43 mmol / g, and the IAST selectivity was 25.2.
[0052] Embodiment 8:
[0053] According to the preparation method in Example 3, lanthanum-doped KIT-6 raw powder with a lanthanum-silicon ratio of 0.08 was prepared.
[0054] Preparation of adsorbent: Weigh 0.2175g (1.1mmol) of copper acetate and 0.5g of La-KIT-6 with a lanthanum-silicon ratio of 0.08, grind them for 30min, heat treat them at 450℃ in air atmosphere for 4h, and obtain a sample loaded with copper oxide after cooling (the mass ratio of copper oxide to carrier is 0.35:1). Take 0.3g of the sample and fill it into a glass capillary, place it in a 140℃ tube furnace for 2h in an ethylene gas flow with a flow rate of 0.5mL / min, and obtain a mesoporous complex adsorbent with highly dispersed active sites after cooling.
[0055] Adsorption application experiment: The gas adsorption performance of the adsorbent was determined by the volumetric method. 500 mg of the above adsorbent was placed in the ASAP2020 specific surface and pore analyzer of Mack, USA, and adsorbed at room temperature and pressure. Finally, the adsorption amount of propylene / propane by the adsorbent was measured respectively, and the propylene / propane separation selectivity of the adsorbent was calculated. At room temperature and pressure, the adsorption amount of propylene by the adsorbent was 4.87 mmol / g, the adsorption amount of propane was 2.47 mmol / g, and the IAST selectivity was 26.8.
[0056] Embodiment 9:
[0057] Laboratory simulation of adsorbent deactivation: Take 0.5g of the cuprous oxide-loaded adsorbent prepared in Example 4, and conduct an adsorption test on ASAP2020. Then, the adsorbent is exposed to the air to deactivate the monovalent copper adsorbent, and a second cycle adsorption test is performed. After 5 cycles, the adsorbent has an ethylene adsorption capacity of 2.21mmol / g, an ethane adsorption capacity of 2.08mmol / g, and an IAST selectivity of 1.12. The adsorbent has been deactivated. The deactivated adsorbent is filled into a glass capillary, placed in a 160°C tubular furnace for 1h in an ethylene gas flow at a flow rate of 5.0mL / min, and an in-situ regenerated cuprous oxide mesoporous molecular sieve adsorbent is obtained after cooling.
[0058] Adsorption capacity test: The gas adsorption performance of the adsorbent was determined by the volumetric method. 500 mg of the above adsorbent was placed in the ASAP2020 specific surface and pore analyzer of Mack, USA, and adsorbed at room temperature and pressure. Finally, the adsorption of ethylene / ethane by the adsorbent was measured respectively, and the ethylene / ethane separation selectivity of the adsorbent was calculated. At room temperature and pressure, the adsorption of ethylene by the adsorbent was 4.30 mmol / g, the adsorption of ethane was 2.20 mmol / g, and the IAST selectivity was 26.1. Compared with Example 4, the adsorption capacity and IAST selectivity of the monovalent copper adsorbent regenerated in situ were the same for ethylene / ethane.
[0059] Embodiment 10:
[0060] Laboratory simulation of adsorbent deactivation: Take 0.5g of the cuprous oxide-loaded adsorbent prepared in Example 8, conduct an adsorption test on ASAP2020, and then expose the adsorbent to the air to deactivate the monovalent copper adsorbent. Perform a second cycle adsorption test. After 5 cycles, the adsorbent has an ethylene adsorption capacity of 2.43mmol / g and an ethane adsorption capacity of 2.23mmol / g. The IAST selectivity is 1.32, and the adsorbent has been deactivated. The deactivated adsorbent is filled into a glass capillary tube, placed in a tubular furnace at 140°C in an ethylene gas flow at a flow rate of 2.5mL / min, and heat treated for 2h. After cooling, an in-situ regenerated cuprous oxide mesoporous molecular sieve adsorbent is obtained.
[0061] Adsorption capacity test: The gas adsorption performance of the adsorbent was determined by the volumetric method. 500 mg of the above adsorbent was placed in the ASAP2020 specific surface and pore analyzer of Mack, USA, and adsorbed at room temperature and pressure. Finally, the adsorption of ethylene / ethane by the adsorbent was measured respectively, and the ethylene / ethane separation selectivity of the adsorbent was calculated. At room temperature and pressure, the adsorption of ethylene by the adsorbent was 4.87 mmol / g, the adsorption of ethane was 2.45 mmol / g, and the IAST selectivity was 26.7. Compared with Example 8, the adsorption capacity and IAST selectivity of the monovalent copper adsorbent regenerated in situ were the same for ethylene / ethane.
Claims
1. A method for preparing a copper-containing mesoporous molecular sieve complex adsorbent, the specific steps of which are as follows: 1) mixing a copper salt with a carrier, grinding them fully, and heat treating them to obtain a mesoporous molecular sieve material with dispersed copper oxide; wherein the mass ratio of copper oxide to the carrier in the prepared mesoporous molecular sieve material with dispersed copper oxide is 0.1 to 1:1; the carrier is a lanthanum-doped mesoporous molecular sieve material with an orderly pore structure, wherein the molar ratio of lanthanum to silicon in the lanthanum-doped mesoporous molecular sieve material is 0.01 to 0.1; 2) The mesoporous molecular sieve material dispersed with copper oxide obtained in step 1) is fixedly placed in an olefin gas flow to perform a reduction reaction to obtain a copper-containing mesoporous molecular sieve complex adsorbent.
2. The preparation method according to claim 1, characterized in that: The copper salt in step 1) is copper nitrate or copper acetate; the heat treatment temperature is 300-600° C. and the time is 2-5 hours.
3. The preparation method according to claim 1, characterized in that The lanthanum-doped mesoporous molecular sieve material described in step 1) is one or both of lanthanum-doped SBA-15 and KIT-6.
4. The preparation method according to claim 1, characterized in that The olefin in step 2) is ethylene or propylene.
5. The preparation method according to claim 1, characterized in that The reduction reaction temperature in step 2) is 100-160°C, the reaction time is 1-2h, and the mass space velocity of the olefin is 0.035-0.875h -1 .
6. A copper-containing mesoporous molecular sieve complex adsorbent prepared by the preparation method as claimed in claim 1.
7. Use of the copper-containing mesoporous molecular sieve complex adsorbent as claimed in claim 6 in olefin-alkane adsorption separation.
8. An in-situ activation and regeneration method for a copper-containing mesoporous molecular sieve adsorbent as claimed in claim 6, characterized in that: The fixed bed with deactivated adsorbent installed is heated to 100-160°C and the mass space velocity of olefin is 0.035-0.875h -1 The reaction was continued for 1 to 2 hours, and the deactivated adsorbent was regenerated in situ.
Citation Information
Patent Citations
Cerium element-modified mesoporous silica adsorbent and preparation method for adsorbent and application in gasoline desulfurization
CN102773072A
Mesoporous complex adsorbent with highly dispersed active sites and preparation method and application thereof
CN112791693A
Preparation method of copper-containing zeolite adsorbent for ethylene-ethane separation
CN117482895A
Preparation method of copper-containing mesoporous molecular sieve adsorbent for olefin-alkane separation
CN117599745A
Rare earth complexing adsorbent, preparation and use in olefin / paraffin separation
CN1680019A